Ocena skuteczności komunikacji marketingowej w social media na przykładzie eventu WAICHL - Siwik, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Internet marketing is becoming more and more popular nowadays, with entrepreneurs increasingly deciding to conduct marketing communication using this medium. The most frequently used tool is social media. Internet marketing creates many opportunities, allowing for the reduction of advertising costs and reaching a much larger number of recipients than traditional advertising. The main purpose of this article is to present the opportunities created by social media both in the context of general promotion and in relation to promoting ascientific event, which is the Wroclaw Annual International Conference on Health and Lifestyle (WAICHL). The article was based on one’s own research, for which it was necessary to plan and conduct communication on social media and analyze the results of the promotion, using the tools offered by Facebook and Instagram, as well as using the Google Analytics platform. The research was based on statistical data on the reactions and behavior of the recipients of the published content. The entire process of creating amarketing communication strategy was presented, and results of activities carried out were summarized, assessing whether social media is an appropriate advertising tool.
Keywords: marketing communication; internet marketing; social media